Perlindungan Hukum Notaris atas Kewajiban Menerapkan Prinsip Mengenali Pengguna Jasa (PMPJ) dan Laporan Transaksi Keuangan Mencurigakan (LTKM) - Saputra, Reynaldo (Jurnal Hukum Caraka Justitia, 2024)
This research analyzes the legal protection of notaries regarding the obligation to apply the principle of recognizing service users and reporting suspicious financial transactions. This research study focuses on whether the obligation to maintain client confidentiality is absolute when faced with a notary's obligation to implement PMPJ and LTKM. Second, what is the legal protection for notaries who implement PMPJ and LTKM obligations? This research is normative, the approach used is statutory and conceptual, and the legal materials used are primary, secondary, and tertiary legal materials collected using library research. The research results show that first, the obligation to maintain client confidentiality is absolute as per the notary's oath of office and UUJN provisions. The obligations of PMPJ and LTKM are the obligations of notaries who act based on contractual relationships with service users, selling and purchasing property, managing financial services and managing company accounts, and establishing, purchasing, and selling legal entities which are not the duties of a notary's position. Second, legal protection for notaries who carry out PMPJ and LTKM obligations receive legal protection provided directly by the state. This form of protection is provided by the state to provide a sense of security for the reporter or witness from possible threats that endanger their person, life, and/or property, including their family. Notaries as reporters and/or witnesses also cannot be prosecuted either criminally or civilly